The Effect of Sleep Time and Learning Duration on Student’s Achievement - Heruna Tanty; Brandon Timotius Santo; Defina Puspita Sari; Eliezeri Yeremi Soeprianto (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2022)
The study was conducted to determine the relationship between study time and sleep time with the Grade Point Average (GPA). Data collection used as many as 103 respondents with a student background majoring in Industrial Engineering at Bina Nusantara University. The results of descriptive statistics show that the average respondent uses 1 to 2 hours of study time per day. The results of descriptive data processing show that the average respondent uses 5 to 7 hours of sleep per day. Inferential statistical results with a correlation test show that there is a correlation between learning activities and sleep with the GPA of Industrial Engineering students at BINUS University. The reliability test showed that there was a correlation between the frequency of sleepiness and the concentration level of students with the acquisition of a Cronbach Alpha score of 0.7277. The reliability test shows that there is a correlation between hours of sleep and the frequency of using the alarm with a Cronbach Alpha value of 0.6363. The reliability test shows that there is a correlation between GPA and the duration of student self-study with a Cronbach Alpha value of 0.6575.